Kebijakan Pemerintah dalam Aktualisasi Pancasila melalui Media Sosial Ditinjau dari Perspektif Sosiologi Komunikasi - Fuqoha Fuqoha; Indrianti Azhar Firdausi (Universitas Serang Raya, 2020)
Pancasila is the philosophy of the Indonesian State as an idiil foundation of Indonesia people. As a State of law, Indonesia has actualized Pancasila in the State's legal system which is the basis for actuallity and achieving the ideals of the nation. The actualization of Pancasila is not sufficiently implemented in the legal order of the State, but must be actualized to each individual as a citizen of the soul value of Pancasila. Social media as a forum to actualize Pancasila for every Indonesian citizen. Through the sociology of communication approach, the actualization of Pancasila through social media can move and foster harmonization in social relations in accordance with the values ​​of Pancasila.